2020
DOI: 10.3389/fphys.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyglutarate Metabolism Is Altered in an in vivo Model of LPS Induced Endotoxemia

Abstract: The metabolic response to endotoxemia closely mimics those seen in sepsis. Here, we show that the urinary excretion of the metabolite 2-hydroxyglutarate (2HG) is dramatically suppressed following lipopolysaccharide (LPS) administration in vivo, and in human septic patients. We further show that enhanced activation of the enzymes responsible for 2-HG degradation, D-and L-2-HGDH, underlie this effect. To determine the role of supplementation with 2HG, we carried out co-administration of LPS and 2HG. This co-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Bone‐marrow derived macrophages (BMDMs) were isolated from femurs and tibias obtained from male mice as previously described (Fitzpatrick et al., 2020). Cells were plated in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% heat‐inactivated fetal bovine serum (FBS), 5% penicillin/streptomycin and 30% conditioned media [media isolated from macrophage colony‐stimulating factor (MCSF) producing L929 cells cultured for 7 days].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone‐marrow derived macrophages (BMDMs) were isolated from femurs and tibias obtained from male mice as previously described (Fitzpatrick et al., 2020). Cells were plated in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% heat‐inactivated fetal bovine serum (FBS), 5% penicillin/streptomycin and 30% conditioned media [media isolated from macrophage colony‐stimulating factor (MCSF) producing L929 cells cultured for 7 days].…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted with TRI Reagent (Sigma, USA) and complementary DNA (cDNA) was generated using a Maxima First Strand cDNA synthesis kit (Thermo Scientific, UK), as previously described (Fitzpatrick et al., 2020). TaqMan probes used were: inducible nitric oxide synthase (iNOS) (Mm00440502), IL‐6 (Mm00446190), IL‐1β (Mm01336189), TLR4 (Mm00445273), and 18S ribosomal RNA (rRNA; 4310893E).…”
Section: Methodsmentioning
confidence: 99%
“…An IDH mutation leads to major metabolic changes involving increased oxidative stress through the reduction of NADPH [52], lactate dehydrogenase A (LDHA) silencing (suggesting that the carbon source is preferentially derived from alpha-ketoglutarate via glutamine metabolism), and PDH suppression (via elevated PDK3 expression) accompanied by increased activity of PC, an essential enzyme for producing intermediate metabolites in various pathways crucial for gluconeogenesis and lipogenesis [53]. Likewise, an IDH mutation increases 2-hydroxyglutarate, a key metabolite during metabolic reprogramming [54].…”
Section: Isocitrate Dehydrogenasementioning
confidence: 99%
“…Apart from its role in oncogenesis, studies have found a physiological role of 2-HG in regulating T cell fate and function, in which accumulation of L-2HG precedes T cell differentiation and alters both T cell metabolism and epigenetics [ 21 , 22 ]. A recent study found decreased production of L and D-2HG in a murine model of lipopolysaccharide-induced endotoxemia, driven by increases in D-2HGDH and L-2HGDH protein levels [ 23 ]. In conclusion, 2-HG is a metabolite with physiological regulatory roles, and alterations in its levels can lead to significant changes in cellular function.…”
Section: Introductionmentioning
confidence: 99%